Pemanfaatan limbah tandan buah kosong kelapa sawit sebagai penguat komposit untuk diaplikasikan sebagai bahan baku outer shell helm Standar Nasional Indonesia (SNI) - Bismantolo, P.; Hestiawan, H.; Wardhani, F.; Utama, M.F. (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2022)
Oil palm empty fruit bunch is abundantly available as waste from palm oil processing which is only used for boiler fuel and plant fertilizers. This study aims to investigate the utilization of oil palm empty fruit bunch as a composite reinforcement material to be applied as a raw material for the outer shell of Indonesian national standard (SNI) helmets. The materials used include oil palm empty fruit bunch, the polyester resin of BQTN yukalac, and the catalyst of MEKPO. The manufacturing process uses the hand lay-up technique by varying the fiber volume fractions 3, 6, 9, 12%, and therefore the fiber size passes mesh of 20 and 50. The tensile test uses the ASTM standard D 638 while the impact test uses the ASTM standard D 5942. Fiber volume fraction and fiber size affect the mechanical properties of oil palm fiber reinforced composites. The results of the tensile and impact tests showed that the highest tensile strength and impact toughness were obtained within the composite with a fiber volume fraction of 6% and a mesh of 50, which were 34.74 MPa and 60.21 kJ/m², respectively. In comparison with the tensile strength of the SNI helmet of 33.93 MPa, the oil palm empty fruit bunch fiber can be used as a composite reinforcement for the outer shell of the SNI helmet.